Efeito da cantaxantina sobre a vida de prateleira e qualidade de ovos de poedeiras comerciais alimentadas com milho ou sorgo - Rosa, Daniele Pozzebon da (2018)
The objective of this study was to evaluate the efficacy of canthaxanthin (CTX) on shelf life and egg quality, stored at two temperatures (4 and 25ºC), of brown hens eggs from 21 to 48 week of age fed with diets based on corn or sorghum. 640 females of the Isa Brown line (21 to 48 weeks of age) were used. A completely randomized experimental design was used in a 2 x 2 factorial arrangement, with two ingredients (corn = CO and sorghum = SO) and supplementation 0 or 6mg/kg CTX, in the periods (P) (I – 21th to 24th, II - 25th to 28th, III - 29th to 32nd, IV - 33rd to 36th, V - 37th to 40th, VI 41st to 44th and VII 45th to 48th week), for performance and quality analysis of fresh eggs (0 d) with 4 treatments and 10 replicates of 16 birds each. For egg quality, the factorial arrangement was the same as before and stored at refrigerated (4ºC) or ambient (25ºC) (2 x 2 x 2) during the shelf life (0, 7, 14, 21 and 28 d) evaluated at the 24th, 32nd, 40th and 48th week of age of the birds. The laying rate was higher for CO + CTX in PII, IV and VI than SO + CTX. Feed intake was higher in birds fed SO in PI, III, IV and VII than CO. Body weight was higher in birds fed CO in PII, IV, V and VI. Feed conversion per dozen eggs and per egg mass were better for CO (P III, IV, PV, VI and VII) than SO. Egg weight at 4ºC was higher at 24th (14, 21 and 28 d), 32nd, 40th and 48th (21 and 28 d) than at 25ºC. The albumen weight at 4ºC was higher at 24th and 40th (14, 21 and 28 d), 32nd and 48th (21 and 28 d) than at 25ºC. Haugh unit was higher at 24th, 32nd, 40th and 48th (7, 14, 21 and 28d) at 4ºC than at 25ºC. The albumen pH at 4ºC was lower at the 24th (07, 14 and 28 d), 32nd, 40th and 48th (7, 14, 21 and 28 d) than at 25ºC. The vitelline membrane strength was higher at 4ºC at 24th and 40th (14, 21 and 28d), 32nd (7d) and 48th (21 d) than at 25ºC. The yolk index was higher in birds fed CO at 24th in shelf life, 32nd (0 and 14 d) and 48th (14 d) than SO. It was also higher at 4ºC in the 24th, 32nd, 40th and 48th (7, 14, 21 and 28 d) than at 25ºC. The yolk color was more intense (orange) in SO+CTX at 24th (0, 07, 14 and 21d), 32nd (0, 21 and 28d), 40th (0, 7, 14, 21 and 28d) and 48th (0d) than SO, CO and CO+CTX, but did not differ from CO + CTX at 24th (28d), 32nd (07 and 14d) and 48th (07, 14, 21 and 28d). The concentration of total carotenoids in the yolk was higher in CO+CTX at 32nd and 40th (0, 7, 14, 21 and 28 d), 48th (0 and 14 d) than SO, SO+CTX and CO. Higher CTX content in the yolk was found in SO+CTX at the 24th, 32nd and 40th days. Lutein and zeaxanthin contents in the yolk were found in CO, at the 24th, 32nd, 40th and 48th days. α-tocopherol content in egg yolks was higher in SO at 24th, 32nd, 40th and 48th weeks of age. Lipid oxidation was lower than the CO+CTX at 48th (0 d). The use of CTX in laying feed promotes an orange color and increases the concentration of carotenoids in the yolk. The temperature has an expressive effect on egg quality parameters.